If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 5 = -6(x + 5) Reorder the terms: 5 + y = -6(x + 5) Reorder the terms: 5 + y = -6(5 + x) 5 + y = (5 * -6 + x * -6) 5 + y = (-30 + -6x) Solving 5 + y = -30 + -6x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + y = -30 + -5 + -6x Combine like terms: 5 + -5 = 0 0 + y = -30 + -5 + -6x y = -30 + -5 + -6x Combine like terms: -30 + -5 = -35 y = -35 + -6x Simplifying y = -35 + -6x
| y=x^3-6x^2+5x+21 | | y+4=-7(x+7) | | X-4=2/5(3-6x) | | -8p-40=8(1-2p) | | (7^2a^2b^5)^-1/(7^-1a^4b^3) | | -7+8r=-3(r+4)+6r | | .75n+9=n+6 | | 1/5*3/4= | | 2x^3+17x^2+38x+15= | | -7k+27=3+4(-2k+5) | | 4(2x-3)+17=29 | | 10x-5+7x=15-2x+4 | | 1/4x-3=2/5 | | 6x/4-2x | | n-2/7=7 | | 195/100 | | 8(X-2)-5x=46 | | 4(2x-3)+1=29 | | 2X+4-X+5=4X | | 0.75=0.4+100 | | 32-8a=-8(4a+2) | | k+45+2k=180 | | 3x^3+6x+9=0 | | b/8-2.6=15.2 | | 145w+36=505 | | 3x^3+6x+9=y | | -6x+6y=-12 | | 5x+12=11?3 | | 505w+36=145 | | 2=m/3-7 | | 145+36=505 | | 505+36=145 |